The Effect of School Supervisors and Principal Managerial Capabilities on Teacher Performance at SMPN 07 Matraman East Jakarta - Rokhmad Slamet; Umi Nihayah (Green Publisher Indonesia, 2021)
Implementation of coaching for teachers is important to do, because teachers are one of the keys to the success of the implementation of education. The purpose of this study was to determine the effect of supervising school supervisors on teacher performance at SMPN 07 Matraman East Jakarta, to determine the effect of principal's managerial ability on teacher performance at SMPN 07 Matraman East Jakarta, to determine the joint effect of fostering school supervisors and the managerial ability of the principal schools on teacher performance at SMPN 07 Matraman, East Jakarta. The type of research used is descriptive quantitative research. The results of this study indicate that there is a positive and significant influence between the guidance of school supervisors on teacher performance at SMPN 07 Matraman, East Jakarta. There is a positive and significant influence between the managerial ability of the principal on the performance of teachers at SMPN 07 Matraman, East Jakarta. There is a positive and significant influence between the coaching of school supervisors and the managerial ability of the principal on teacher performance at SMPN 07 Matraman, East Jakarta.